Enhanced photocatalytic performance for oxidation of glucose to value-added organic acids in water using iron thioporphyrazine modified SnO2. Issue 18 (20th August 2019) - Zhang, Quanquan; Ge, Yanchun; Yang, Changjun; Zhang, Bingguang; Deng, Kejian
Abstract : Photocatalytic oxidation of glucose to value-added organic acids in water was realized by SnO2 /FePz(SBu)8 using atmospheric air as the oxidant. Abstract : The selective conversion of glucose into value-added chemicals in the presence of only water is a challenging topic. In this work, selective photocatalytic oxidation of glucose in water was studied using iron thioporphyrazine modified SnO2 (SnO2 /FePz(SBu)8 ) as the catalyst and atmospheric air as the oxidant under simulated sunlight irradiation. It was found that value-added organic acids including glucaric acid, gluconic acid and formic acid could be obtained from the oxidation of glucose under such conditions. The effects of the FePz(SBu)8 content, glucose concentration and additional addition on the conversion of glucose and the selectivity of the organic acids were further explored. Under the optimized conditions, the total selectivity for the organic acids on the SnO2 /FePz(SBu)8 photocatalyst reached up to 52.2% at 34.2% glucose conversion. More importantly, it has been demonstrated that the presence of FePz(SBu)8 on the surface of SnO2 can keep the selectivity of the organic acids unchanged under conditions of increasing the glucose conversion. To illustrate the synergistic effect for the enhanced photocatalytic activity between FePz(SBu)8 and SnO2, surface photocurrent, electron spin resonance (ESR) spectra and adsorption behavior experiments were carried out on pure SnO2 and SnO2 /FePz(SBu)8 . It was found that the introduction of FePz(SBu)8 could enhance the separation of photogenerated charge, promote the generation of active species for photocatalysis and improve the adsorption capacity of glucose, which are beneficial to the enhancement of photocatalytic activity. Additionally, a possible pathway of glucose oxidation was proposed through both detailed analysis of the oxidation intermediate of glucose and comparative experiments with different organic acids as the substrates, indicating that the formation of organic acids were fulfilled by two parallel and subsequent reactions at the beginning of the reaction.